Analisis Kinerja Pajak Hotel dan Pajak Restoran Pasca Pandemi Covid-19 di Kota Malang - Puspita, Wulan Dri; Lakaq, Maria Charolina Ina; Asa, Maria Nidya (JURNAL ONLINE INSAN AKUNTAN; Vol 10 No 1 (2025): Jurnal Online Insan Akuntan (Juni 2025), 2025)
This research aimed to analyze the tax performance of hotels and restaurants during and after the COVID-19 pandemic. The growth ratio and effectiveness ratio were used to analyze the financial performance. Descriptive quantitative methods were used as the research method by using data from Local Government Malang's financial reports from 2020 to 2023. This research stated that the tax revenue of hotels and restaurants from 2020 to 2021 were decrlining. Although both taxes were increased in 2022, but those were declined again in 2023. The tax revenue of hotel was classified as very effective only in 2023. Restaurant tax revenue was classified as very effective from 2020, 2021, and 2022. Meanwhile, in 2023 the restaurant tax revenue was classfied as effective.   Keywords : Analyze, Tax, Hotel, Restaurant